1985
DOI: 10.1111/j.1745-6592.1985.tb00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations at Sites Contaminated with Dense, Non‐Aqueous Phase Liquids (NAPLs)

Abstract: Increasingly, ground water supplies are being found to be contaminated with organic substances. Depending on the nature of these substances and the method by which they were introduced into the environment, they may form a second, dense liquid phase. Several such cases have been reported in the recent literature. In other cases, such a second phase might have actually been present but was not found because the principles governing its distribution were not understood and no effort was made to look for it. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 11 publications
0
24
0
1
Order By: Relevance
“…A large number of groundwater contamination events result from nonaqueous phase liquids (NAPLs) in the groundwater [Burmaster and Harris, 1982;Feenstra and Coburn, 1986;Villaume, 1985;Mackay and Cherry, 1989;Feenstra and Cherry, 1988]. Mackay and Cherry [1989] report that organic contaminants are the most common health-threatening chemicals detected in groundwater, and that NAPLs comprise much if not most of this contamination.…”
Section: ! Introduction and Backgroundmentioning
confidence: 99%
“…A large number of groundwater contamination events result from nonaqueous phase liquids (NAPLs) in the groundwater [Burmaster and Harris, 1982;Feenstra and Coburn, 1986;Villaume, 1985;Mackay and Cherry, 1989;Feenstra and Cherry, 1988]. Mackay and Cherry [1989] report that organic contaminants are the most common health-threatening chemicals detected in groundwater, and that NAPLs comprise much if not most of this contamination.…”
Section: ! Introduction and Backgroundmentioning
confidence: 99%
“…Primary sources of organic chemical pollution of the subsurface include: seepage from unlined lagoons and other surface impoundments; improper landfUling; improper surface and subsurface disposal practices; leaks in pipes, storage tanks, and other processing or transport equipment; and accidental spills (1 (11)(12)(13)(14). In these case studies, significant vertical and lateral transport of NAPL is documented.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…In these case studies, significant vertical and lateral transport of NAPL is documented. Other representative case studies involving multiphase transport may be found in (11,(15)(16)(17)(18).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Extensive aquifer contamination by chlorinated solvents has been described by Raux and Althoff (1980). Villaume (1985) describes several cases of nonaqueous phase contamination by 1.3 disposal of coal tar on the soil surface and by injection wells, spilled PCBs, and a nondescript, liquid mixture of organic fluids lea~ed from a pond.…”
Section: Case Studiesmentioning
confidence: 99%
“…This value of saturation where the fluid becomes discontinuous is called the residual saturation. For subsurface contamination systems where an immiscible organic liquio phase is present, the dispersal of the organic liquid can eventually lead to isolated parcels of fluid with organic liquid saturations averaging approx~ mately 10% (Villaume 1985} but possibly reaching as high as 40% in the saturated zone (Wilson and Conrad 1984). In reality, how~ver, movement of these isolated parcels of fluid can occur, resulting in a process termed "blob flow."…”
Section: Blob Flowmentioning
confidence: 99%